A critical evaluation of the role of iron overload in fatty liver disease. Issue 10 (16th August 2022) - Fernandez, Monique; Lokan, Julie; Leung, Christopher; Grigg, Andrew
Abstract: Nonalcoholic fatty liver disease (NAFLD) has been associated with a condition known as the dysmetabolic iron overload syndrome, but the frequency and severity of iron overload in NAFLD is not well described. There is emerging evidence that mild to moderate excess hepatic iron can aggravate the risk of progression of NAFLD to nonalcoholic steatohepatitis and eventually cirrhosis. Mechanisms are postulated to be via reactive oxygen species, inflammatory cytokines, lipid oxidation, and oxidative stress. The aim of this review is to assess the evidence for true hepatic iron overload in NAFLD, to discuss the pathogenesis by which excess iron may be toxic, and to critically evaluate the studies designed to deplete iron by regular venesection. In brief, the studies are inconclusive due to heterogeneity in eligibility criteria, sample size, randomization, hepatic iron measurement, serial histological endpoints, target ferritin levels, length of venesection, and degree of confounding lifestyle intervention. We propose a trial designed to overcome the limitations of these studies.